CORPORATE SOCIAL RESPONSIBILITY OF BUSINESS IN UKRAINE DURING THE WAR - MOROZ, Sergiy; MEISH, Alla; LEVCHENKO, Sofia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Corporate social responsibility is a strategic concept that defines the obligations of enterprises to contribute to the humanitarian development of society and the natural environment. In Ukraine, enterprises consider social responsibility as an integral part of business culture, it has undergone significant changes since the beginning of the war with russia. The annexation of Crimea in 2014 and the russian invasion of Ukraine on February 24, 2022 caused a deep humanitarian crisis and growing socio-economic challenges. In this regard, Ukrainian companies are forced to reconsider their approaches to corporate social responsibility. Many entrepreneurs and businesses have redirected their efforts to providing humanitarian aid and resources to affected areas and refugees. This led to an increase in their influence on improving the state of social security and a decrease in the impact of military events on the local population.Ukrainian companies also paid more attention to the environmental aspect of corporate social responsibility, as military actions led to the deterioration of the environment and threats to people's health. Enterprises intensified their participation in projects for ecological restoration and development of renewable energy, cleaning of contaminated lands, demining of territories, restoration of chemical production facilities and oil product storage bases.The growing interest in corporate social responsibility has also led to greater transparency in the activities of enterprises and the desire to create trust among consumers. Many companies have begun to actively publish reports on their social and environmental achievements, disclosing information about their activities and the extent of their impact on society and the environment.In general, the war with russia caused a rethinking of approaches to corporate social responsibility in Ukraine, forcing companies to place greater emphasis on the humanitarian aspect and environmental responsibility. These changes contributed to improving the quality of life of the population, became more environmentally oriented, and also contributed to increasing trust between companies and society.
Keywords: corporate social responsibility; economic; environmental; ethical; social responsibility; business; war; migration; property inequality; poverty; social injustice